Implementasi Sistem Informasi Akuntansi Penjualan dan Pembelian Menggunakan Metode Extreme Programming (Studi Kasus Toko Sumber Sayur) - Riva Nursari Patunisa; Ari Sudrajat (Universitas Methodist Indonesia, 2025)
Sales and purchasing are the main activities of companies, especially trading companies. One of the techniques needed by trading companies to support business activities is the use of an appropriate accounting information system. Accounting information is closely related to business activities, because with accounting information the company can see the condition of the company's development so that it can be used as a source for decision making so that the company's goals can be achieved. The simple process of recording sales and purchase transactions using book media can cause various problems in reporting sales and purchase transactions and is ineffective. The Sumber Sayur Store in running its business still uses a conventional sales and purchase transaction recording system, namely recording using books. This is very detrimental and inefficient. The system was built using the Extreme Programming software development method. Based on the results of research and system testing, it can be concluded that this system can help overcome problems in sales and purchase transactions effectively with the results of system testing using the User Acceptance Test of 87,33%.